PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF DENGAN PENDEKATAN DEEP LEARNING BERBANTUAN GOOGLE SITES PADA MATERI JURNAL PENYESUAIAN KELAS XI AKUNTANSI DI SMKN 4 SURABAYA - Elvira Nurul Aulia; Irwan Adimas Ganda Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Advancements in science and technology (IPTEK) within the education sector have transformed the way students learn, shifting from conventional methods to flexible, open, and information technology-based learning. However, many educators still fail to fully utilize technology, resulting in monotonous instruction. This study aims to develop and assess the feasibility of a Google Sites-based learning medium covering the topic of adjusting entries for Grade XI Accounting students at SMKN 4 Surabaya. The study employs the Research and Development (R&D) method using the ADDIE development model, which comprises the stages of Analysis, Design, Development, Implementation, and Evaluation. During the analysis phase, the researcher conducted observations and interviews with both educators and students. The learning medium was designed to accommodate students' learning styles. The developed product underwent review by subject matter and media experts to ensure the quality of the content and the visual interface. Data collection involved the use of expert validation sheets and student response questionnaires based on a Likert scale. The study participants consisted of 30 Grade XI Accounting students. Expert validation results indicated that the developed learning medium achieved scores of 94.6% from the subject matter expert and 96% from the media expert, yielding an average of 95.3%—placing it in the "highly feasible" category. Furthermore, student response to the medium showed a 90% rating, falling into the "excellent" category. Consequently, this interactive Google Sites-based learning medium is deemed suitable for use as a learning resource.